2006
DOI: 10.1002/app.23023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the process on phase separation induced by radical copolymerization of styrene and divinylbenzene in the presence of reactive polyurethane network precursors

Abstract: ABSTRACT:Interpenetrating polymer systems based on crosslinked polyurethane (PU) and polystyrene (PS) were prepared at room temperature by a one-shot (in situ) method, starting from an initial homogeneous mixture of reagents via noninterfering mechanisms. Both polymerizations were performed either simultaneously or one after the other. True simultaneity at every stages of the process is not possible. Despite the difference in refractive index of the components, hazy or optically clear films were obtained, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…[13] Mechanical properties in IPNs can be tailored by controlling the morphology, or more specifically, the degree of mixing. [13][14][15][16][17][18][19][20] Early work by Widmaier and coworkers demon strated that the degree of mixing between two polymer networks could be manipulated kinetically during the formation of the two networks. [16,[21][22][23] Recently the use of orthogonal Access to multimaterial polymers with spatially localized properties and robust interfaces is anticipated to enable new capabilities in soft robotics, such as smooth actuation for advanced medical and manufacturing technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Mechanical properties in IPNs can be tailored by controlling the morphology, or more specifically, the degree of mixing. [13][14][15][16][17][18][19][20] Early work by Widmaier and coworkers demon strated that the degree of mixing between two polymer networks could be manipulated kinetically during the formation of the two networks. [16,[21][22][23] Recently the use of orthogonal Access to multimaterial polymers with spatially localized properties and robust interfaces is anticipated to enable new capabilities in soft robotics, such as smooth actuation for advanced medical and manufacturing technologies.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Mechanical properties in IPNs can be tailored by controlling the morphology, or more specifically, the degree of mixing. [ 13–20 ] Early work by Widmaier and coworkers demonstrated that the degree of mixing between two polymer networks could be manipulated kinetically during the formation of the two networks. [ 16,21–23 ] Recently the use of orthogonal chemistry in forming IPNs has gone a step further to investigate how differences in initiation and propagation can control morphology, and as a result, mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The number of additional entanglements between unlike chains increases with increasing cross-link density of the primary PU network. For the same system both polymerizations were performed either simultaneously or one after the other [306]. It was discovered that the degree of phase separation depends on the experimental conditions.…”
Section: Kinetics Of Formation Of Sequential Ipnsmentioning
confidence: 98%